The effectiveness of use of peat’s biologically active substances in feeding of bulls - R. V. Rusakov; A. V. Vylegzhanin (Аграрная наука Евро-Северо-Востока, 2017)
The purpose of the research is to evaluate the effectiveness of bulls-producers feeding with biologically active food supplements with antioxidant properties derived from peat as to the quality of sperm. The study was carried out in 2016 by the method of group-periods (preliminary, experimental and final) in specialized breeding enterprises of the Kirov region. It was formed 2 analogous groups of animals - experimental and control one - 10 animals each. In the experimental period of 30 days the animals of the experimental group were fed with the studied Supplement containing 8.3% of humic and 24.7% fulvic acids in an amount of 50 ml per head per day mixed with feed. In the preliminary and final periods of 60 days each, the Supplement is not used. The studies established that the complex of substances with antioxidant properties that are included in the supplements had a positive effect in maintaining the high quality of the sperm of animals. In the experimental period, the concentration of sperm in the ejaculate of bulls that received feed additive increased by 0.07 billion/ml or 7.4%; in the final period by 0.08 billion/ml or 8.4% (p